(untitled) (World Bulletin of Management and Law, 2023)
The main objective of this study is to investigate the impact of unemployment on Jordan’s economy over the period 1991–2019. This study used the autoregressive distributed lag (ARDL) model to investigate the relationship between the unemployment rate and the other variables. Also, we employ the ARDL bootstrap cointegration approach to examine the correlation and longrun relationship among the variables. The empirical fnding indicated a longrun relationship between the unemployment rate, economic growth.